1992
DOI: 10.1007/bf00123320
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the rooting patterns of some agroforestry trees in an arid region of north-western India

Abstract: The present study deals with root architecture of 6-year-old trees of 9 indigenous and 3 exotic species growing in and climate of north-western India. Observations, made on excavated root systems (3 tree rephcates of each species) showed large variation in horizontal and vertical spread of roots. In Morus alba, Melia azedarach and Populus deltoides, the roots were confined to 80 cm, while m Prosopis cineraria, Acacia nilotica and Eucalwtus terettcornis, roots penetrated more deeply to 233 cm. The number of tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 26 publications
3
27
0
1
Order By: Relevance
“…During the first years, the low branches [34] and low diameter growth in relation to the tree's height [7] prevent teak from having the morphological structure required to support the moments created by the wind against the biomass accumulated in the upper parts of the tree, which bends the stem without causing uprooting, as normally occurs with this species.…”
Section: Discussionmentioning
confidence: 99%
“…During the first years, the low branches [34] and low diameter growth in relation to the tree's height [7] prevent teak from having the morphological structure required to support the moments created by the wind against the biomass accumulated in the upper parts of the tree, which bends the stem without causing uprooting, as normally occurs with this species.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reports (Jones et al, 1998;Canadell et al, 1996) that roots of trees and shrubs can reach a depth of more than 10 m and in some cases more than 30 m below ground. In absence of effective management many trees root in surface soil and outcompete crops though the depth to which trees root depends on the availability of soil water and nutrients in the soil profile, which itself is affected by crop uptake (Sinclair et al, 2000).Greater SWC in top soil layer in P. cineraria plot might also be due to soil water use by this species from deeper soil layers because of deep rooting behaviour of P. cineraria (Shankarnarayan et al, 1987;Tejwani, 2001;Toky and Bist, 1992). Increased SWC with increase in growth of P. cineraria tree (Figure 6a) may also be related to its capacity to absorb water through foliage during rain (Bhatt and Lahiri, 1964), which was relatively greater in September than in August 2013 (Figure 1b).…”
Section: Soil Water Contentmentioning
confidence: 99%
“…This zone contained an average of 43% of total leucaena roots. Other observations made by Toky and Bisht (1992) were that between 78 to 84 % of the total root biomass were contained from the surface to 0.3 m depth. Whereas, Dhyani and collaborators (1996) found that L.…”
Section: Below-ground Interactionsmentioning
confidence: 93%
“…Lateral root spread of leucaena (28 months old) was 1.35 m (Dhyani et al 1999), while Toky and Bisht (1992) observed 1.43 m of horizontal root movement in leucaena 6 years old. According to Govindarajan (1996), leucaena root spread in 4 year old trees was relatively low (1.5 m) in comparison to single leucaena trees (same age) with more than 2 m of spread; however root spread declined drastically beyond 2.5 m.…”
Section: Below-ground Interactionsmentioning
confidence: 99%
See 1 more Smart Citation